2021
DOI: 10.3390/biomedicines9080875
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Gut Microbiota in Schizophrenia and Treatment Resistance to Antipsychotics

Abstract: The gut microbiota is constituted by more than 40,000 bacterial species involved in key processes including high order brain functions. Altered composition of gut microbiota has been implicated in psychiatric disorders and in modulating the efficacy and safety of psychotropic medications. In this work we characterized the composition of the gut microbiota in 38 patients with schizophrenia (SCZ) and 20 healthy controls (HC), and tested if SCZ patients with different response to antipsychotics (18 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The significant potential of psychotic drugs to alter gut microbial composition in vitro has been observed by Macedo et al [ 54 ] and Maier et al [ 55 ]. An altered composition of gut microbiota in schizophrenia patients has also been observed very recently by Manchia et al [ 56 ]. The composition of gut microbiota in 38 schizophrenia patients, 20 health controls, 18 patients with treatment-resistant schizophrenia (TRS), and 20 responders (R) to different antipsychotics has been investigated in detail.…”
Section: Antipsychotics-induced Side Effects and Gut Microbiota Dysbi...supporting
confidence: 58%
“…The significant potential of psychotic drugs to alter gut microbial composition in vitro has been observed by Macedo et al [ 54 ] and Maier et al [ 55 ]. An altered composition of gut microbiota in schizophrenia patients has also been observed very recently by Manchia et al [ 56 ]. The composition of gut microbiota in 38 schizophrenia patients, 20 health controls, 18 patients with treatment-resistant schizophrenia (TRS), and 20 responders (R) to different antipsychotics has been investigated in detail.…”
Section: Antipsychotics-induced Side Effects and Gut Microbiota Dysbi...supporting
confidence: 58%
“…The 15 studies examining the gut microbiota in SZ were published between 2018 and 2021, with sample sizes ranging from 26 to 214 participants, again predominantly conducted in China (80%; N = 12/15 studies) (Table S3 ). Five studies included subgroups: first-episode or treated-SZ [ 99 ], acute-episode or in symptomatic remission [ 101 , 112 ], treatment resistant or treatment responders [ 109 ] and baseline or after treatment [ 111 ]. Overall, 15 studies in SZ including a total of 20 comparison groups were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, most studies excluded controls with other physical or systemic illnesses (80%; N = 12/15 studies). However, three studies did not exclude some cardiometabolic conditions and reported their presence in the results [ 100 , 107 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations